Reversible Watermarking Techniques: An Overview and a Classification. (14th June 2010) - Caldelli, Roberto; Filippini, Francesco; Becarelli, Rudy
Abstract : An overview of reversible watermarking techniques appeared in literature during the last five years approximately is presented in this paper. In addition to this a general classification of algorithms on the basis of their characteristics and of the embedding domain is given in order to provide a structured presentation simply accessible for an interested reader. Algorithms are set in a category and discussed trying to supply the main information regarding embedding and decoding procedures. Basic considerations on achieved results are made as well.